Polymeric nanoparticles promote macrophage reversal from M2 to M1 phenotypes in the tumor microenvironment. (January 2017) - Wang, Yi; Lin, Yao-Xin; Qiao, Sheng-Lin; An, Hong-Wei; Ma, Yang; Qiao, Zeng-Ying; Rajapaksha, R.P. Yeshan J.; Wang, Hao
Abstract: Immunotherapy has shown promising treatment effects for a variety of cancers. However, the immune treatment efficiency for solid tumors is limited owing to insufficient infiltration of immune cells into solid tumors. The conversion of tumor-supportive macrophages to tumor-suppressive macrophages, inducing the functional reversal of macrophages, is an effective method and contributes to a subsequent antitumor response. The current challenge in the field is the poor distribution and systemic side effects associated with the use of cytokines. As a solution to this issue, we designed and synthesized microenvironment-responsive nanoparticles (P) with IL-12 payload (IL-12⊂P1). These nanoparticles could promote the systemic administration and release of IL-12 in the tumor microenvironment, and the locally responsive property of IL-12⊂P1 could subsequently re-educate tumor-associated macrophages (TAMs). In particular, our results illustrated the great therapeutic effects derived from the functional conversion of macrophages. Our strategy was to design a microenvironment-responsive material for local macrophage modification to overcome the physiological barrier of solid tumors. The shifting of macrophage phenotypes via IL-12⊂P1 achieved immunomodulation in the microenvironment for cancer therapy, with negligible cytotoxicity. We expect that the functional regulation of TAMs by pH-responsive nanomaterials is a promising therapeutic approach for cancer immunotherapy.